2010
DOI: 10.1021/pr100963n
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Cellular Response to Novel Proapoptotic Agents Related to Atypical Retinoids in Human IGROV-1 Ovarian Carcinoma Cells

Abstract: Novel agents characterized by the scaffold of the atypical retinoid ST1926, but containing different chemical functions (carboxylic or hydroxamic acid), exhibit potent proapoptotic activity. In the present paper, we show that the treatment of the IGROV-1 ovarian cancer cell line with compounds sharing structural features with ST1926 (ST1898, ST3595, ST3056) determines a strong inhibition of proliferation mainly due to apoptotic cell death. In an effort to understand the mechanism of action of these compounds, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 89 publications
3
8
0
Order By: Relevance
“…In this study, we showed that ST1926 potently inhibited the growth and induced massive apoptosis of ATRA-resistant AML cells at low sub-mmol/L concentrations through the activation of DNA damage and dissipation of the mitochondrial membrane potential. This ST1926 mechanism of action is similar to previously reported results in other tested hematological malignancies (13,22,(24)(25)(26) and solid tumors (16,19,21,23,46). Importantly, sub-mmol/L ST1926 concentrations exerted the same inhibitory effect in primary AML patients' derived blasts, while sparing normal leukocytes and normal human hematopoietic and MSCs.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, we showed that ST1926 potently inhibited the growth and induced massive apoptosis of ATRA-resistant AML cells at low sub-mmol/L concentrations through the activation of DNA damage and dissipation of the mitochondrial membrane potential. This ST1926 mechanism of action is similar to previously reported results in other tested hematological malignancies (13,22,(24)(25)(26) and solid tumors (16,19,21,23,46). Importantly, sub-mmol/L ST1926 concentrations exerted the same inhibitory effect in primary AML patients' derived blasts, while sparing normal leukocytes and normal human hematopoietic and MSCs.…”
Section: Discussionsupporting
confidence: 88%
“…We found that ST1926 effectively inhibits both ERMS and ARMS cell proliferation, exerting its effects by activating the DDR pathway, resulting in a combination of S‐phase arrest and inhibition of cell cycle progression, and induction of apoptosis. This is similar to its mechanism of action in other cancer cell lines, including leukemia and some solid tumors . In our study, ST1926 induced a prominent DDR both in treated RMS cells in vitro and in xenografts in vivo , with phosphorylation of H2AX, ATM and ATR substrates, as well as p53 protein.…”
Section: Discussionsupporting
confidence: 85%
“…In RMS, retinoic acid has shown some activity in inhibiting proliferation and inducing differentiation in vitro , however the effects are of low magnitude, and do not translate into tumor control in vivo in mouse xenograft studies, partly due to incomplete cell cycle exit despite evidence of enhanced differentiation . More potent synthetic retinoids have been developed, and some were found to exhibit mechanisms of action independent of retinoic acid receptor signaling pathway, resulting in growth inhibitory and proapoptotic activity . Prototypes of atypical retinoids—also known as retinoid‐related molecules (RRM)—are CD437 and its analog ST1926, which shows more favorable pharmacokinetic profile than CD437 and is orally bioavailable .…”
mentioning
confidence: 99%
“…844 In the human ovarian cancer cell line IGROV-1, retinoids 428 – 430 have been studied, identifying them as growth inhibitors for the cancer cells (IC 50 ( 428 ) = 0.21 ± 0.06 μM; IC 50 ( 429 ) = 1.31 ± 1.31 ± 0.2 μM; IC 50 ( 430 ) = 0.62 ± 0.2 μM). 845 They share mechanism of action and their influence on gene expression as shown by proteomics; a majority of the proteins whose expression is influenced by these latter three retinoids have a role in Ca 2+ homeostasis regulation. SHP, the probable target protein of the adamantyl retinoids, also is of significance in metabolic anormalities such as diabetes, fatty liver, and insulin resistance; therefore, SHP regulation is a valuable goal in these fields also.…”
Section: Adamantane Derivatives In Cancer Researchmentioning
confidence: 99%